2008
DOI: 10.1243/09544119jeim431
|View full text |Cite
|
Sign up to set email alerts
|

Wear simulation of ultra-high molecular weight polyethylene hip implants by incorporating the effects of cross-shear and contact pressure

Abstract: The effect of multi-directional cross-shear (CS) motion and contact pressure on ultra-high molecular weight polyethylene (UHMWPE) wear was investigated in this study, based on an integrated experimental and computational approach. The wear factor as a function of CS was determined experimentally from a multi-directional pin-on-plate wear tester under a nominal contact pressure of 1 MPa. A computational wear model was developed which included the effects of CS as well as the load and sliding distance imposed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
83
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(92 citation statements)
references
References 30 publications
9
83
0
Order By: Relevance
“…However, an increasing wear rate was seen in the 5DOF tests, which may be due to an increasing contact area, which was supported by the wear scar measurements. In opposition to classical wear theory (Archard's wear law) [29], increased contact area has been shown to increase polyethylene wear rates [30], provided that the contact stress is still below the yield stress, which would otherwise lead to fatigue failure. Archard's law holds true for cases where the asperity contacts deform plastically, such as in metallic contacts.…”
Section: Discussionmentioning
confidence: 95%
“…However, an increasing wear rate was seen in the 5DOF tests, which may be due to an increasing contact area, which was supported by the wear scar measurements. In opposition to classical wear theory (Archard's wear law) [29], increased contact area has been shown to increase polyethylene wear rates [30], provided that the contact stress is still below the yield stress, which would otherwise lead to fatigue failure. Archard's law holds true for cases where the asperity contacts deform plastically, such as in metallic contacts.…”
Section: Discussionmentioning
confidence: 95%
“…Flexion/extension (15°-30°) and internal/external rotation (± 10°) were applied to the components, the combination of which resulted in the production of both open elliptical and figure of eight wear paths on the surface as described previously [1,10] Microseparation was produced on the Leeds Mk II hip simulator by applying a small lateral load to the cup causing approximately 0.5 mm medial and superior translation of the cup relative to the head during swing phase, as described previously [16] with the cup positioned at an inclination angle of 55°. Wear was determined gravimetrically after 1 million and 2 million cycles for the high cup and microseparation studies and at 1 million, 2 million, and 5 million cycles for the standard conditions study using methods reported previously [13].…”
Section: Methodsmentioning
confidence: 99%
“…In other words, use of these variables as inputs to the computational wear model, along with load and sliding distance, and the predicted wear can be independently validated against separate hip simulator conditions. To date, the effect of cross-shear on the computational wear modelling has only been considered for the hip (Kang et al, 2008a) and knee joint (Hamilton et al, 2005;Knight et al, 2005). The effect of both cross-shear and contact pressure-dependent wear factor has not been considered previously in computational wear modelling of polyethylene hip implants.…”
Section: Introductionmentioning
confidence: 99%